The Associations Between Physical Performance and Anthropometric Characteristics in Obese and Non-obese Schoolchild Handball Players - Hermassi, Souhail; van den Tillaar, Roland; Bragazzi, Nicola Luigi; Schwesig, René (Frontiers in Physiology, 2021)
This study investigated the relationship of body fat and field measures of physical fitness in youth handball players. Twenty-eight young male handball players from handball first youth league volunteered for the present investigation (age: 10.9 ± 0.72 years; body mass: 54.8 ± 22.9 kg; height: 1.48 ± 0.10 m; body fat: 27.6 ± 9.23 %). Measures included the Yo-Yo Intermittent Recovery Test level 1 (Yo-Yo IR1), jumping ability (squat and counter-movement jumps (SJ, CMJ), and sprint tests (10 m, 15 m). Anthropometry was assessed by body mass, fat percentage (%BF), and body mass index (BMI). Power of upper limb was measured as the total distance thrown overhead using a 2-kg medicine ball. Intrarater reliability for all parameters showed a coefficient of variation (CV) below 10% and an intraclass correlation coefficient (ICC) above 0.75. All ICC were excellent (ICC≥0.96). Reliability as shown by the CV differed between 1.0 (sprint 15 m) and 5.6 (sprint 10 m). With the exception of medicine ball throw, we found significant differences between non-obese and obese in all performance parameters. The differences ranged from sprint 10 m (p2=0.47) to medicine ball throw (p2=0.09). The two-step-linear regression analysis (step 1) predictors: body height and body weight; (step 2) predictors examined the unique contribution of %BF showed a marked increase of explained variance by adding body fat. The largest r2 changes were calculated for sprint 10 m (0.54), CMJ (0.49) and sprint 15 m (0.42). The lowest influence of the predictors was observed for medicine ball throw (step 1: r2=0.03, step 2: r2=0.07). With the exception of sprint parameters (-coefficient sprint 10 m: -0.74; -coefficient sprint 20: -0.66), a decrease of %BF leads to a higher performance in all parameters. %BF in youth handball players should be an important concern for practitioners working in this team sport in contrast to the frequently used BMI. It seems sensible and appropriate to engage very young children in physical activities such as team handball in order to improve their physical fitness. Optimizing % body fat should be considered as a training and nutrition goal in order to improve sport performance.